Pengembangan E-government dalam Layanan Kartu Identitas Anak (KIA) Kota Tangerang : Studi Kasus pada Pengembangan Layanan Aplikasi Identitas Kependudukan Digital - Raveena Aprilia; Agus Suherman; Muhammad Ibrahim Rantau (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Public service is an activity to fulfill community needs provided by government agencies. The community certainly needs the best quality service. Until now, the public considers that the government has slow, wasteful and functional bureaucratic performance. People often complain about the complexity of processing population documents. One of Indonesia's population documents is the Child Identity Card. Efforts to develop the implementation of government on an electronic basis to realize improvements in the quality of public services effectively and efficiently are called E-government. The Tangerang City Population and Civil Registration Service is implementing the Digital Population Identity application as an e-government implementation to serve the community. However, there are still several problems with implementing this application, namely that people are worried about data security, the application sometimes experiences problems, and the Child Identity Card service features are still incomplete. The aim of the research carried out is to find out how the e-government development process at Child Identity Cards Tangerang City is based on the use of the Digital Population Identity application and what the supporting and inhibiting factors are. This research is of a qualitative type with a descriptive method that uses the results of analysis from Indrajit's theory (2016) which has three aspects of success in developing e-government, including Support, Capacity and Value. This analysis shows that the development of e-government at Child Identity Cards Tangerang City using the Digital Population Identity application has not been successful because there are several obstacles that must be corrected.